The Effect of Earth's Magnetic Field on the HF Radio Wave Modes at the Heated Subionosphere - Canyilmaz, M.; Atici, R.; Guzel, E. (Polish Acad Sciences Inst Physics, 2013)
In this study, the effect of the actual geometry of the magnetic field on the electron temperature has been investigated daily and seasonally for the electromagnetic wave travelling at subionosphere. The electron energy balance equation has been obtained by using the ideal gas approximation. The results show that there are notable differences between the two situations (B parallel to k parallel to z and B real, parallel to z). According to our theoretical study, the maximum changes are shown at L- and R-mode, small effect on X-mode and no variation on O-mode due to the real geometry of the magnetic field. Besides, the heights of the maximum points are changeable daily and seasonally for all modes at the subionosphere.
Keywords: Lower Ionosphere; Tromso; Temperature